The Effect of Service Quality, Doctor Interpersonal Communication, and Customer Relationship Management on Patient Loyalty with Patient Satisfaction as A Mediation at RSUBUDI Rahayu Pekalongan - Jefly Mandala Putra; Suliyanto; Gunistiyo; Aminul Fajri (Faculty of Economics and Business, University of Pancasakti Tegal, 2022)
The aims of this research were to the effect of service quality on patient satisfaction, the effect of doctor's interpersonal communication on patient satisfaction, the influence of customer relationship management on patient satisfaction, the effect of service quality on patient loyalty, the effect of doctor's interpersonal communication on patient loyalty, the effect of customer relationship management on patient loyalty, the effect of patient satisfaction on patient loyalty, the effect of service quality on patient loyalty with patient satisfaction as a mediator, the effect of interpersonal communication of doctors on patient loyalty to patient satisfaction as a mediator, the effect of customer relationship management on patient loyalty is patient satisfaction as a mediator. The population in this study were all inpatients at RSU Budi Rahayu Pekalongan. The number of inpatients at Budi Rahayu Hospital in Pekalongan in October 2022 was 450 patients. The sampling technique used was purposive sampling. The technique used to collect data in this study is a questionnaire. The data analysis method of this research is to test the validity and reliability of the instrument, descriptive statistics, and quantitative analysis.